THE NUMBER OF EXTRANODAL SITES IN NODAL PTCL: A PROPOSAL FOR A FEASIBLE PROGNOSTIC MARKER FOR OUTCOMES IN LOW-INCOME COUNTRIES. A COLLABORATIVE STUDY GRUPO DE ESTUDIO LATINO-AMERICANO DE LINFOPROLIFERATIVO (GELL) & T-CELL BRAZIL PROJECT (TCBP) - T Fischer; E Miranda; J Pereira; G Duffles; JV Tavares; NS Castro; RSA Silva; DLC Farias; SAB Brasil; CCG Macedo; C Colaço; RLR Baptista; et al. (Hematology, Transfusion and Cell Therapy)
Introduction: PTCL accounts for 10-15% of all NHL. As previously demonstrated, Latin America has its own epidemiological distribution, with a high frequency of ATLL and ENKT, likely influenced by distinct genetic profiles and viral epidemiology. 3-year OS is about 40%. Treatment advances have also been limited, except for BV-CHP in some countries. The IPI, which includes extranodal (EN) site as a variable, has been validated for PTCL. However, the specific impact of EN involvement on nodal PTCL (such as PTCL-NOS, AIT, ALCL ALK+/ALK-) and its biological implications remain unclear. Simplification could improve the reproducibility and applicability of these models, especially in low-income countries. Objective: To evaluate number of EN sites in nodal PTCL lymphomas as a risk factors or surrogate for outcomes, as OS and PFS in Latin America cohort. Methodology: Patients (pts) aged ≥18 years with newly diagnosed nodal PTCL-NOS, AITL and ALCL ALK+/ALK-) from GELL (n = 339, 2000-2023, retrospective), TCBP (n = 427, 2015-2022, ambispective). Treatment outcome was determined by OS and PFS. REDcap Platform (by Vanderbilt) was used to collect and store data, whereas statistical analysis the IBM-SPSS v.24. This trial is registered at Clinical trials (NCT03207789). Results: 766 pts [427pts - TCBP and 339 - GELL] diagnosed with nodal PTCL were grouped according to the number of EN: no EN involvement (No EN - 383); one EN involvement (EN1 -168); and 32 (EN2 - 215). Considering all, 61% male; median age 56 y/o; 74% were staged III/IV; 69% IPI 32; 60% was PTCL-NOS, 19% ALCL ALK- and 12% AITL. 61% had B symptoms and 55% elevated LDH. CHOEP was used in 47% and 34% CHOP, and 47% achieved CR after first line; 16% used transplant as consolidation. No EN, EN1 and EN2 were similar regarding clinical characteristics, except, for stage III/IV (58% vs. 79% vs 96%; p < .0001); IPI 32 (58% vs. 59% vs. 99%; p < .0001); ECOG>1 (58% vs. 92% vs. 99%; p < .0001); BMO involvement (16% vs. 24% vs. 63%%; p <.0001), elevated LDH (54% vs. 47% vs. 61%; p =.03) and Hypoalbuminemia (33% vs. 38% vs. 58%; p <.0001). NHL-T subtypes showed better OS and ALCL ALK+ better PFS. Among No EN, EN1 and EN2 the response CR after 1st line had a statistically difference (54% vs 46% vs 37%, p = 0.002), 60-month OS (45% vs. 44% vs. 27%, p <.0001) and PFS (31% vs. 34% vs. 18%; p <.0001). Conclusion: EN2 presented more advanced disease, with possible distinct biology, hence, the number of EN involvements can be useful as a practical and informative surrogates for outcomes, suggesting number of EN sites involvement assessed by CT and PET-CT as feasible clinical surrogate for outcomes in this population. New biomarkers are essential to better stratify patients with PTCL. Still, in practice, it is also necessary to have ways to stratify these patients using clinical data, mainly in regions with low-income resources. These indicators reflect distinct biological characteristics that merit further molecular investigation, potentially enhancing tailored therapies. Registries are essential given the rarity and poor prognosis associated with these diseases as well as generate hypotheses.